Parametric finite element analysis of punching shear behaviour of RC slabs reinforced with bolts. (February 2020) - Navarro, M.; Ivorra, S.; Varona, F.B.
Highlights: Numerical analysis of punching shear behaviour of retrofited RC slabs. A Concrete Damage Plasticity model has been calibrated. Qualitative and quantitative calibration with experimental results by other authors. Parametric study to analyse the influence of different retrofiting configurations. Optimal configuration and spacing between shear bolts are proposed. Abstract: Reinforced concrete slabs are an essential part of high-rise structures and are designed to withstand the loads to which they are subjected. However, concrete slabs may fail due to punching shear, which is one of the greatest risks they face. This type of failure, hard to predict, befalls almost instantaneously and may lead to catastrophic consequences. In this paper, ABAQUS is used to analyse a series of non-linear numerical models to simulate the punching shear effect on reinforced bolt-retrofitted concrete flat slabs whose bolts are arranged in three different positions around the support. To start with, an initial calibration of a finite element model was carried out with experimental results reported by Adetifa and Polak. Next, a parametric analysis was performed to determine the influence of the retrofitting geometrical parameters. For this purpose, over two hundred models were created with the help of an automation algorithm programmed in Python. Our parametric study shows that a shear-bolt radial layout may be most adequate for retrofitting slab-to-column connections in which the phenomenon of punching shear is likely to occur. Moreover, the distance between the first pair of bolts and the column's face is recommended to be approximately five times the diameter of the shear bolts.